IMF Staff papers, Volume 45 No. 3. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1998)
This paper presents international evidence on the determinants of trade dynamics. It provides some new empirical perspectives on the relationship between international trade and macroeconomic fluctuations in industrial economies. A comprehensive set of stylized facts concerning fluctuations in trade variables and their determinants is presented. A measure of the quantitative importance of international trade for the propagation of domestic business cycles is then constructed, focusing on the role of external trade as a catalyst for cyclical recoveries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet